Investigating the relationship between test anxiety and ambiguity tolerance on EFL learners’ performance in written classroom assessment - Hussien Jawad Abdulridha; Umulbaneen Alaulddin Salih; Wrood Hashim Altaai; Ruqayay Raad Kadhim; Raneem Hussein Aliwi; Zainab Ali Adnan Abdul-Hur (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2026)
This study examined the relationships between test anxiety, ambiguity tolerance and written classroom assessment performance among EFL university students. The data were gathered using Westside Test Anxiety Scale and Second Language Ambiguity Tolerance Scale along with a 15-mark written classroom assessment. Descriptive statistics were used to report the means and ranges of test anxiety and ambiguity tolerance; the results showed that most students reported high levels of test anxiety and that the levels of ambiguity tolerance varied. Correlational analyses indicated a small but statistically significant negative correlation (r = −.25, p < .05) between test anxiety and tolerance for ambiguity. Multiple regression analysis indicated that the combination of test anxiety and ambiguity tolerance explained 36% of the variance in written assessment performance (R² = .36). Finally, test anxiety was found to be a statistically significant negative predictor of students' written assessment scores, while ambiguity tolerance was a statistically significant positive predictor. Notably, students who achieved the highest scores exhibited the lowest levels of test anxiety and the highest levels of ambiguity tolerance. The results indicate that both emotional and cognitive factors are important predictors of written English as a Foreign Language (EFL) assessment performance.